On the spiders of the ground layer of a pine forest in Finnish Lapland, with notes on their diurnal activity - Koponen, Seppo (Reports from the Kevo Subarctic Research Station, 1972)
Abstract: The material, consisting of 38 species of spiders and 390 specimens, was collected using pitfall traps in June and July 1968, at Kevo, Finnish Lapland. The family Linyphiidae was most dominant (about 60 % of specimens) and the most abundant species were Hilaira herniosa, Pardosa eiseni, Hahnia ononidum, and Lepthyphantes decipiens. Some notes on the distribution and the diurnal activity of the spider fauna are also provided.
Keywords: 1970-luku; 1970-talet; selkärangattomat; hämähäkit; havumetsät; lajit; ryggradslösa djur; spindlar; barrskogar; arter; Kevo (Utsjoki); Lappi; Utsjoki; Lappland